2003
DOI: 10.1242/jeb.00706
|View full text |Cite
|
Sign up to set email alerts
|

Influences of thermal acclimation and acute temperature change on the motility of epithelial wound-healing cells (keratocytes) of tropical,temperate and Antarctic fish

Abstract: SUMMARYThe ability to heal superficial wounds is an important element in an organism's repertoire of adaptive responses to environmental stress. In fish,motile cells termed keratocytes are thought to play important roles in the wound-healing process. Keratocyte motility, like other physiological rate processes, is likely to be dependent on temperature and to show adaptive variation among differently thermally adapted species. We have quantified the effects of acute temperature change and thermal acclimation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…However, studies on cellular dynamics have shown that actin-dependent motility, resulting in significant changes in cell morphology, is strongly attenuated at reduced temperatures, with a Q 10 of ϳ4 ranging from 29 to 39°C (Hartmann-Petersen et al, 2000). Similar values have been recorded for epithelial cells from various teleosts (Ream et al, 2003).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, studies on cellular dynamics have shown that actin-dependent motility, resulting in significant changes in cell morphology, is strongly attenuated at reduced temperatures, with a Q 10 of ϳ4 ranging from 29 to 39°C (Hartmann-Petersen et al, 2000). Similar values have been recorded for epithelial cells from various teleosts (Ream et al, 2003).…”
Section: Introductionsupporting
confidence: 60%
“…A possible explanation for this striking difference in cold sensitivity lies in the contrast in cytoskeletal structure between the dendritic spine, which is based on filamentous actin, and the dendrite shaft where microtubules predominate (Matus et al, 1982;Halpain, 2000;Kaech et al, 2001). The high content of dynamic actin filaments in dendritic spines not only drives their high motility (Fischer et al, 1998) but also renders them sensitive to the low temperature, which inhibits actin filament dynamics resulting in reduced cell motility (Pollard, 1976;HartmannPetersen et al, 2000;Ream et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A paradigm system for actin based cell motility is the fish epidermal keratocyte Ream et al, 2003), a cell that moves smoothly, (with speed circa 0.25 µm/s (Laurent et al, 2005)) while retaining a typical crescent shape. This mode of cell motion is not restricted to keratocytes, as other cell lineages can present this behaviour as well (see Discussion).…”
Section: Actin Cytoskeletonmentioning
confidence: 99%
“…However, as temperature increases, the rate of responses accelerates (Roberts 1989). For example, Ream et al (2003) showed that as temperature increased, so did the motility of epithelial wound-healing cells (keratocytes), which migrate across wounded areas to inhibit infection (Radice 1980a(Radice , 1980bEuteneuer and Schliwa 1984). Anderson and Roberts (1975) found the White Cloud Mountain minnow (Tanichthyes albonubes) experimentally wounded (2-4 mm long, 0.6-1 mm deep) with a scalpel healed more quickly when held at elevated temperatures than the Atlantic salmon (Salmo salar) held at lower temperatures.…”
Section: 2mentioning
confidence: 99%